2021
DOI: 10.37064/jpm.v9i2.9769
|View full text |Cite
|
Sign up to set email alerts
|

Peran Sirkular Sampah Produk Untuk Meningkatkan Produktivitas Usaha Masyarakat Desa Bagorejo

Abstract: The application of the waste bank is essentially a social engineering that encourages people to sort their waste. This study aims to analyze the management of the Waste Bank in Ampeldento Hamlet, Bagorejo Village, Gumukmas District, Jember Regency. In addition, this research will be implemented to analyze the social, economic and environmental impacts of waste banks in Ampeldento Hamlet, Bagorejo Village, Gumukmas District. The method using quantitative and qualitative. The implementation of data search activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…In analyzing the six sigma method, an initial stage is needed to define the value of product defects, so the first step is to collect analytical data related to the percentage of defects product as in the table. 3 In Table .3 the most dangerous level of defects occurs in November as big at 5.03%, as well as the level of product, lowest occurred in month October at 2.80%. height product of 5.03% should be overcome and minimized, as evidenced by the level of product disabled Lowest as big as 2.80% with this thing a company in implementation should be capable carry out the process production with a defect level of 2.80%.…”
Section: A Define Stagementioning
confidence: 92%
See 1 more Smart Citation
“…In analyzing the six sigma method, an initial stage is needed to define the value of product defects, so the first step is to collect analytical data related to the percentage of defects product as in the table. 3 In Table .3 the most dangerous level of defects occurs in November as big at 5.03%, as well as the level of product, lowest occurred in month October at 2.80%. height product of 5.03% should be overcome and minimized, as evidenced by the level of product disabled Lowest as big as 2.80% with this thing a company in implementation should be capable carry out the process production with a defect level of 2.80%.…”
Section: A Define Stagementioning
confidence: 92%
“…Therefore the company must anticipate the competitive market by favoring quality product that is guaranteed and according to the expectations of consumers. Because quality is a key company in getting the trust of consumers [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Masalah sampah menjadi tanggung jawab pemerintah dan warga masayarakat yang dimulai dari hulu, proses dan hilir (Elamin et al 2018). Sampah berpotensi untuk meningkatkan produktivitas usaha untuk meningkatkan perekonomian masyarakat pedesaan (Firmansyah, Herlambang, and Sumarmi 2021).…”
Section: Sirkular Ekonomi Lokalunclassified
“…The findings of empirical research have demonstrated that quality of the environment and public health will be affected if the amount of waste continues to grow unchecked and is not appropriately managed [7]. In other words, ineffective and inefficient waste management that does not employ environmentally friendly waste management methods and technology has a negative influence on population health and can contaminate the environment [8]. This, for example, has occurred in the subdistrict of Rawa Pitu, which has a population of 18,114 and generates numerous types of organic and inorganic trash [9].…”
Section: Introductionmentioning
confidence: 99%
“…There are a great number of studies on the circular economy, but each one focuses on a different aspect, such as the research carried out by [8] which emphasizes on the function that product waste can play in a circular economy to boost the productivity of enterprises located in rural regions. Other studies [8], [33] put an emphasis on developing waste management practices that are consistent with a circular economy, the potential for the reuse of plastic grocery bags [34]- [36], the transformation of organic waste into goods with marketable worth [37], the proper disposal of glass bottles [38], household waste management strategies [39], circular economy-based waste management comprehension of rural communities [40], constructing a network of waste banks as a solution for waste management and as a means of establishing a circular economy for people in communities other than their own [41], social, economic, and demographic aspects of circular migratory decision-making [42], [43], and the influence of circular migration on the socioeconomic circumstances of migrant households [44], [45]. However, to the best of our knowledge, research on sustainable development in transmigration areas has not yet been conducted on the circular economy.…”
Section: Introductionmentioning
confidence: 99%